(untitled) (Archives of Clinical Psychiatry, 2017)
Background: Only 29% of cannabis dependent individuals seek treatment, yet significant decreases in cannabis use are seen in 31-36% of individuals that seek treatment. Follow-up studies have found that over 60% in substance use disorders end in relapse, leading to potentially chronic and relapsing cases. New and effective therapies should be researched in order to increase the success of relapse prevention treatments. Objective: In this study we aimed to evaluate the relationship between trait mindfulness level, substance dependence severity and quitting cannabis use. Methods: A hundred and sixty four patients, diagnosed with cannabis dependence, were involved in the study; socidemographic datas were recorded and Addiction Profile Index (API), Mindfuness Attention and Awareness Scale (MAAS) were carried out. Results: We found that the trait mindfulness level is significantly related with quitting cannabis use. Discussion: Trait mindfulness may be an important determining factor of the ability to quit substance use and achieve remission.